Financial Literacy and the Continued Use of Paylater Services: An Application of the Theory of Planned Behavior - Fauzia G, Frisca; Nidya, Firdiyanti; Tandra, Geraldi; Gunadi, Willy (Jurnal Locus Penelitian dan Pengabdian, 2025)
Digitalization is now increasingly widespread, accelerating the transformation of the traditional financial industry to become more innovative and efficient through the presence of financial technology (fintech). One of the fastest-growing fintech services today is paylater, a short-term financing innovation that allows consumers to buy now and pay later. This study aims to examine the factors influencing the sustainable use of paylater by integrating the Theory of Planned Behavior (TPB) with the variables of Fear of Missing Out (FOMO), hedonic motivation, and financial literacy as moderators. Data collection was conducted through the distribution of online questionnaires involving 150 Generation Z respondents aged 19–25 years in the Jakarta and Tangerang areas, all of whom had used paylater in the last three months. This research uses a quantitative approach with the Partial Least Squares Structural Equation Model (PLS-SEM) analysis method. The results indicate that attitude, subjective norm, and perceived behavioral control (PBC) significantly and positively influence the continuous use of paylater. However, FOMO, hedonic motivation, and financial literacy do not significantly moderate the relationship between attitude and continuous usage.